Dr. Atkins' age-defying diet revolution - Atkins, Robert C.; Buff, Sheila (New York : St. Martin's Press, 2000)
Staving off the affects of aging is the main concern of the dietitian's new book, which covers cardiovascular disease, cancer, stroke, diabetes, and brain function, among other physical problems associated with growing older. Simultaneous.
Part I. An Introduction to Defying Aging -- Part II. Why We Age -- Part III. Age-Defying Nutrients -- Part IV. Techniques to Defy Aging -- Part V. Living the Age-Defying Diet.
Includes bibliographical references and index.
Keywords: AGING -- NUTRIENTS ASPECTS